Przewalski`s horse (Equus ferus przewalskii) in the Chornobyl Exclusion Zone after 20 years of introduction - Gashchak, S.P.; Paskevich, S.A. (Theriologia Ukrainica, 2019)
Camera traps (CT) were used in 2018 to assess the current state of the Przewalski’s horse (PH) population. Przewalski’s horses were introduced into the Ukrainian Chornobyl Exclusion Zone (CEZ) in 1998. Up to 720 km2 (of the 2 600 km2 total CEZ area) were investigated between February and November 2018, however the assessment reported here was made between May–July when PH are more settled with regards to the territory used. Totally 137 PH were recorded in the Ukrainian part of the CEZ: 47 stallions, 66 mares (adult & fillies) and 24 foals (10 males, 4 females and 10 of unidentified gender). At least four more PH (stallion, 2 mares, 1 foal) are noted at a remote site in the Belarus CEZ (V. Dombrovsky, or. rep.). All foals were born April-July 2018. There were 13 harem herds with foals (3–16 individuals in total in each), four small non-breeding groups (2-3 individuals), ca. 6 stallion groups (2–6 individuals), and at least one solitary stallion. Harem and non-breeding herds generally kept to ca. 18 sites, stallion groups normally roamed. Two-three groups lived on territories which including both Ukrainian and Belorussian parts of the CEZ. During 2007–2010 PH crossed the river Prypiat and finally founded a local reproducing sub-population. Almost all PH are from the 2nd and higher generations, only two mares had a brand mark which identified the original introduced population. One herd (Ilintsy) includes a domesticate breed mare (in autumn she moved to a neighbouring group, in Stechanka, where in 2019 gave birth to a hybrid foal sired by the Ilintsy stallion). At least, two males (solitary stallion and colt) had signs of hybridization (i.e. PH and domesticated horse). Underestimation of the total PH population in our study is likely as not all appropriate sites were investigated. The total herd, as identified here, of PH grew seven-fold between 1998 and 2018. However, the rate of population increase between 2009–2018 was in 1.5 times less than that 1998–2008 previously reported. This reduced population growth rate was likely due to the changing age structure of the herd, the initial herd contained only older (more productive) mature mares, over time numbers of younger (less productive) mares increased. The present demographic indices and reproductive potential do not indicate any negative tendencies in the population development, and evidence the further fitness to the local conditions. PH are native to open steppe landscapes and our study confirms their preference to meadows in the CEZ. However, we observed that PH do not avoid forests. Reforestation of meadows and predominance of woodlands in the CEZ are obstacles for comprehensive monitoring of PH, and may contribute to an underestimation of the population size as direct visual observations do not work well in the woodlands. CT studies offer a solution to this problem. Фотопастки (ФП) використано у 2018 р. для оцінки поточного стану популяції коней Пржевальського (КП), інтродукованих до Чорнобильської зони відчуження (ЧЗВ) у 1998 р. Обстежено до 720 з 2600 км2 загальної площі у період з лютого до листопада, проте представлена тут оцінка зроблено для травня-липня, коли КП найбільш осілі. На український частині ЧЗВ нараховано 137 КП: 47 жеребців, 66 кобил (дорослих і незрілих), і 24 лоша (10 самців, 4 самки, і 10 невизначеної статі). Щонайменше 4 ще (жеребець, 2 кобили і 1 лоша) відмічені на віддаленій ділянці Білорусі (усн. повід. В. Домбровського). Всі лошати народилися у квітні–липні. Було 13 гаремних табунів з лошатами (по 3–16 особин в кожному), 4 малих нерепродуктивних табуни (2–3 ос.), близько 6 жеребцевих груп (2–6 ос.) і щонайменше один звичайно одинокий жеребець. Гаремні і нерепродуктивні табуни трималися на 18 ділянках. Жеребцові групи звичайно кочували. Дві-три групи жили на ділянках, що включають і українську, і білоруську частини. У 2007–2010 роках КП переткнули р. Прип’ять і остаточно сформували місцеву субпопуляцію. Майже всі КП відносяться до другого і вище покоління, лише дві кобили мають тавро отримане до інтродукції. Один табун у Іллінцях мав домашню кобилу (восени вона перейшла до сусідньої групи у Стечанці, де у 2019 р. принесла лоша від жеребця з Іллінців). Щонайменше 2 самця (один дорослий негаремний і один нестатевозрілий) мали ознаки гібридизації з домашнім конем. У даному досліджені можливе деяке заниження загальної оцінки поголів’я, оскільки не всі придатні ділянки були обстежені. Як визначене, поголів’я КП зросло у 7 разів з 1998 по 2018 рік. Проте, приріст у 2009–2018 роках був у 1,5 рази менший за той, про який повідомлялося у 1998–2008 роках. Таке уповільнення росту можливо стало результатом зміни вікової структури популяції. У первинній групі було більше зрілих і більш плодовитих кобил, тоді як з часом частка молодших і менш продуктивних кобил збільшилася. Теперішні демографічні показники та репродуктивний потенціал не мають ознак негативного розвитку популяції, і вказують на подальше пристосування КП до місцевих умов. КП є представниками відкритих степових комплексів, і наші дослідження підтверджують їх перевагу до луків ЧЗВ. Проте, ми виявили, що КП не уникають і лісів. Лісовідновлення і перевага лісових земель є головними перепонами для всебічного моніторингу КП, і можуть викликати заниження оцінок розміру популяції, оскільки можливості для прямих спостережень у лісі обмежені. ФП дозволяють вирішити цю проблему.